2012
DOI: 10.1103/physrevb.86.024103
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous to crystalline phase transition in carbon induced by intense femtosecond x-ray free-electron laser pulses

Abstract: We present the results of an experiment where amorphous carbon undergoes a phase transition induced by femtosecond 830 eV x-ray free-electron laser pulses. The phase transition threshold fluence is found to be 282 ± 11 mJ/cm 2 . Atomic force microscopy, photoelectron microscopy, and micro-Raman spectroscopy give experimental evidence for the phase transition in terms of a volume expansion, graphitization, and change of local order of the irradiated sample area. The interaction is modeled by an accurate time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
(42 reference statements)
1
25
0
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38][39][40] The main intent of the work is to investigate and detail the route of graphitization from the amorphous to the graphitic phase by different schemes of temperature and/or pressure loading of the material. The role of the atomic density of the material during the transformation is delineated and ultimately, an atomic density "window" at which there is optimal graphitization for a particular predefined set of loading conditions is established.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32][33][34][35][36][37][38][39][40] The main intent of the work is to investigate and detail the route of graphitization from the amorphous to the graphitic phase by different schemes of temperature and/or pressure loading of the material. The role of the atomic density of the material during the transformation is delineated and ultimately, an atomic density "window" at which there is optimal graphitization for a particular predefined set of loading conditions is established.…”
Section: Objectivesmentioning
confidence: 99%
“…When the excitation is sufficiently large, a nonthermal phase transition occurs. 36,37 On a similar note, instead of an optical excitation, graphitization can also be activated by ion irradiation. Kim et al reported that during the process of ion bombardment, the stopping of the electrons by the amorphous carbon atoms provides energy for the phase transformation.…”
Section: Introductionmentioning
confidence: 99%
“…It is important that the contamination layer should be characterized properly before applying a suitable cleaning process since carbon in diamond like (DLC) form is more tightly bonded; the layer is likely to be more difficult to clean. Gaudin et al experimentally observed solid-to-solid phase transition from amorphous carbon to graphite nanocrystal by intense femtosecond x-ray free electron laser pulses [17]. If we understood the properties of these types of contamination layer then its cleaning technique (such as UV/O 3 cleaning for soft layers like polymeric layers and laser or plasma based cleaning for hard layers like DLC) can be easily selected to remove the contamination layer.…”
Section: Introductionmentioning
confidence: 98%
“…When subjected to intense XFEL pulses, graphite and amorphous carbon have recently been shown to exhibit some highly unusual properties ( 7 , 8 ). Here, we demonstrate that during interaction with a highly focused, high-energy pulse of x-rays, crystalline C 60 undergoes a marked transition to an electronic state of lower symmetry.…”
Section: Introductionmentioning
confidence: 99%